2013
DOI: 10.1016/j.diii.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of second intra-tendinous platelet-rich-plasma injection in case of incomplete response of the first injection: Three-year follow up experience

Abstract: Our study suggests that second early intra-tendinous PRP injection under US guidance does not permit rapid decrease of tendinopathy area in US, nor does it quickly improve clinical pain and functional data in case of incomplete efficiency of first PRP injection. However, in long-term follow-up, patients improved their ability to mobilize pathologic tendons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…The adequate number of injections over time is also a point of debate in naturally occurring human tendinopathy: In a long term clinical trial in humans it was shown that a second early PRP injection does not rapidly improve clinical signs of tendinopathy in case of incomplete resolution after the first treatment [65]. However, it has been shown in a controlled human clinical trial that patients with chronic patellar tendinopathy receiving two injections of a leucocyte poor platelet concentrate (autologous conditioned plasma®) showed better improvement in outcomes when compared to a monoinjection [66].…”
Section: Discussionmentioning
confidence: 99%
“…The adequate number of injections over time is also a point of debate in naturally occurring human tendinopathy: In a long term clinical trial in humans it was shown that a second early PRP injection does not rapidly improve clinical signs of tendinopathy in case of incomplete resolution after the first treatment [65]. However, it has been shown in a controlled human clinical trial that patients with chronic patellar tendinopathy receiving two injections of a leucocyte poor platelet concentrate (autologous conditioned plasma®) showed better improvement in outcomes when compared to a monoinjection [66].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a 3-year follow-up case series study emphasizes the potential importance of a second PRP injection in painful tendon tears unresponsive to a single injection. 35 A recent cross-sectional retrospective survey gathered outcome data from different tendons treated with PRP. In this study involving a total of 180 patients, 106 patients were treated for PT and more than 80% of patients who received one or two injections and 76% of those who received three injections reported moderate-to-complete resolution of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Reports assessing autologous blood, PRP or varicose vein-sclerosing drugs, injected in different sites (intra, peritendinous) under different conditions (clinically-guided, imaging-guided), in heterogeneous populations, including patients with T+ and patients with rupture, with no long term follow-up and no histological examination 9,22,23 have provided contradictory results. Thus, there is no clear conclusion regarding the curative effect of PRP in T+.…”
Section: Discussionmentioning
confidence: 99%